The induction effect: why the rebound effect is only half the story of technology's failure to achieve sustainability - Lange, Steffen; Frick, Vivian; Gossen, Maike; Pohl, Johanna; Rohde, Friederike; Santarius, Tilman (Frontiers in Sustainability, 2023)
The concept of the rebound effect is important in understanding the limits to how much technological efficiency improvements can reduce energy and resource consumption. However, due to the concept's focus on efficiency, it neglects other environmental implications of technological change. We use the term 'induction effect' to grasp additional important mechanisms stemming from new technologies. We define an induction effect as an increase in the level of energy or resource consumption that was caused or enabled by the emergence of 'new options' arising from technological change. Our investigation of three cases of new technologies -online consumption, smart homes, and pace of life -shows how including both rebound and induction effects into the analysis helps in understanding the relationship between technological change and energy and resource consumption. Integrating induction effects into the analysis underpins the importance of sufficiency as a strategy for sustainability and helps to develop comprehensive policy measures.